2021
DOI: 10.1098/rsta.2020.0082
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification in classical molecular dynamics

Abstract: Molecular dynamics simulation is now a widespread approach for understanding complex systems on the atomistic scale. It finds applications from physics and chemistry to engineering, life and medical science. In the last decade, the approach has begun to advance from being a computer-based means of rationalizing experimental observations to producing apparently credible predictions for a number of real-world applications within industrial sectors such as advanced materials and drug discovery. However, key aspec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(147 citation statements)
references
References 113 publications
(179 reference statements)
7
137
3
Order By: Relevance
“…One of these, ESMACS [2,14,16,17,19] (enhanced sampling of molecular dynamics with approximation of continuum solvent), uses ensembles of multiple and typically relatively short duration simulations to calculate absolute binding free energies with high precision. There is a wealth of evidence in the literature and in unpublished work that, under equilibrium conditions, multiple short MD simulations sample better than a single long MD simulation and provide a meaningful uncertainty of the results [8,9,2022]. Under general non-equilibrium conditions, ensembles are essential since there is then no meaning to time averaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these, ESMACS [2,14,16,17,19] (enhanced sampling of molecular dynamics with approximation of continuum solvent), uses ensembles of multiple and typically relatively short duration simulations to calculate absolute binding free energies with high precision. There is a wealth of evidence in the literature and in unpublished work that, under equilibrium conditions, multiple short MD simulations sample better than a single long MD simulation and provide a meaningful uncertainty of the results [8,9,2022]. Under general non-equilibrium conditions, ensembles are essential since there is then no meaning to time averaging.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that single long time simulations are inaccurate, as we have explained before (e.g. [22]). Ensembles are required for all MD simulations [20,22], as precise predictions, along with their uncertainties, can be obtained only when the most relevant conformations have been extensively sampled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used ensemble-based ESMACS and TIES for the free energy calculations. Extensive studies have confirmed that the most effective and reliable computational route to reproducible predictions using MD simulation can be achieved using ensemble methods 23 , 39 41 . A set of independent MD simulations are employed to obtain the required averages and associated uncertainties.…”
Section: Methodsmentioning
confidence: 98%
“…Wan et al [5] discuss the quantification of uncertainty in simulations that are based on classical molecular dynamics. The paper addresses simulations in a wide range of applications from binding affinity calculations for drug discovery to properties prediction within condensed matter and materials.…”
mentioning
confidence: 99%